Effect of FW conditions on mechanical and microstructural characteristic of AA6061/SiC/Graphite hybrid composites joint by empirical relationship. (16th December 2021) - Senthilkumar, J; M, Bakkiyaraj; Balasubramanian, M; Loganathan, T G
Abstract: Friction welded AA6061 matrix hybrid composite joints were investigated to understand the process effect on the metallurgical properties with the aid of empirical relationships. SiC of 10% with the standard particle size of 25 μ m and 5% graphite with the particle size of 30 μ m were added into the AA6061 matrix. The investigation has 20 sets of experiments as per the matrix designed. Each process condition, namely rotation speed (N), upset load (F), and upset time (T), as well as their impact on joint properties, were investigated individually, with the estimated tensile strength correlated to their corresponding metallographic properties. The observation of this study concludes that the disparity in grain size is mainly affected by the availability of heat sources and the plasticized material during the friction stage and it is highly influenced by rotation speed. Furthermore, the lower level parameters produce the defective joint while the higher level parameters are attributed to ejecting the extensive amount of hot material from the joint interface. Finer reduction in grain size of 1.5 μ m and ample plasticized material consolidation at the optimized welding conditions of 1600 rpm rotation speed, 3.5 kN upset load, and 4 s upset time were attributed to achieving the maximum tensile strength of 167 MPa.